Methods for xylitol recovery: Appraisal and future perspectives - Martinez, E. A.; Dussán, K. J. [UNESP]; Silva, D. D.V. [UNESP]; Souza, R. L.; Prata, A. M.R. (Springer Nature, 2022)
The recovery of a product obtained by a biotechnological process can represent from 30 to 90% of the total cost of the process, depending, among other factors, on the type of product and the degree of purity necessary to make its use viable. The recovery of xylitol obtained by bioprocess is not yet technologically established, both because of the complexity of the raw materials used in the process and the purity required, as it is a food grade product. There is a range of key operations for the recovery of a bioproduct and, for xylitol, crystallization seems to be of great importance today and, apparently, the most promising. In this chapter, initially an introduction to the recovery and purification of bioproducts in general is presented, aiming to allow a connection with the strategies that will be presented for the case of xylitol. Then, the most relevant works found in the literature so far are discussed, showing the updated panorama. Emphasis was given to crystallization as a key operation for obtaining xylitol in commercial form. Finally, some future perspectives regarding the recovery and purification of xylitol obtained by biotechnological process were discussed.
Keywords: Bioproducts; Crystalization; Downstream; Lignocellulosics; Raw materials; Xylitol